Nine perfect strangers - Moriarty, Liane (New York : Flatiron Books, 2018)
c
Keywords: Novelists -- Fiction; Health resorts -- Fiction; Strangers -- Fiction; Interpersonal relations -- Fiction; City dwellers -- Fiction; Psychological fiction; Thrillers (Fiction).; Suspense fiction